Pengaruh Tingkat Pendidikan, Upah, dan Migrasi Terhadap Pengangguran di Kota Makassar - Juardi, Juardi; Arifai, Arifai; Umar, Mustofa (OIKONOMIKA : Jurnal Kajian Ekonomi dan Keuangan Syariah, 2023)
This research aims to find out that the problem of unemployment does not only affect economic life. Apart from that, the problem of unemployment is also closely related to the educational and social fields. In the current era, not only people with low education are unemployed, but more and more people with higher education are also unemployed. So researchers researched to determine the influence of education level, wages, and incoming migration on unemployment in Makassar City. This research uses quantitative research. This research uses quantitative research and the data used is secondary data, where secondary data is data contained in the media such as data from the central statistical agency and from online news and data in the form of complete data recording reports. Data was obtained from the Central Statistics Agency (BPS) and the population and civil registration service in the period 2007-2022. The data analysis method used in this research is the multiple linear regression method using the Statistical Program For Social (SPSS) software method. The estimation results show that: The education level variable has an effect on unemployment in Makassar City, the Wage variable has no effect in Makassar City and the Incoming Migration variable has no effect on unemployment in Makassar City